INACTIVE HEPATITIS B CARRIER AND PREGNANCY OUTCOMES - Anwar, Rabiah; Razzaq, Kashif (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the impact of hepatitis B carrier status on pregnancy and perinatal outcome.Study Design: Cross sectional study.Place and Duration of Study: Department of Gynaecology and Obstetrics, Pakistan Naval Ship Shifa Hospital,Karachi, from Feb 2017 to Jan 2018.Methodology: A total of 9526 women delivered during study period. 9305 women fulfilling the inclusion criteriawere included in study. Two hundred and twenty one (221) women were excluded because of not fulfilling theinclusion criteria. Out of study group, 9104 women were HBsAg negative while 201 had positive hepatitis Bcarrier status. Antenatal complications (such as gestational diabetes, gestational hypertension, pre eclampsia),mode of delivery (vaginal delivery, elective cesarean, emergency cesarean) and perinatal outcomes (pretermdelivery, low birth weight at delivery, live birth rate, APGAR score at 1 and 5 min) were observed amonghepatitis B carrier and noncarrier.Results: There was no significant difference in point prevalence of major antenatal complications, mode ofdelivery and perinatal outcomes in HBsAg carriers and noncarriers. A slightly higher rate of preterm birth wasobserved in hepatitis B carriers (4.9%) as compared to noncarriers (2.6%).Conclusion: Hepatitis B carriers have slightly increased risk of preterm delivery.